Evaluation of abrasive mechanisms in metallic alloys during scratch tests: a numerical-experimental study in micro-scale. - Seriacopi, Vanessa (2017)
The abrasion can have some approaches, such as: (i-) the manufacturing processes and the production of different surface features and finishing of workpieces and components; and (ii-) in terms of the wear and failure, which occur in tools materials. The present thesis consists in developing a numerical model by Finite Element Method (FEM) validated by experimental tests, aiming to evaluate microstructural influences on the abrasion of metallic alloys. Therefore, objectives are related to define rules focused on ductile material design to obtain cutting resistance. Regardless of their applications, the abrasive micro-mechanism depends on mechanical and damage properties of the materials and their microstructure. A simplified abrasion study is developed considering a single abrasive over a microstructure to evaluate from ploughing to cutting. Thus, scratch tests are performed in micro-scale, applying different ranges of constant normal force. Moreover, the specimen characterization was conducted using optical and electronic microscopy techniques, optical interferometry, conventional hardness, and instrumented indentation. By the developed numerical approach, the results were: (a-) in terms of apparent coefficient of friction (COF), the found numerical and experimental mismatches are assigned to the effects of adhesion, anisotropy, grain boundaries and twinning, for instance, which were not taken into account on the modelling; (b-) the hard precipitates have a prevailing effect over the matrix regarding the apparent COF, whereas the matrix effect is dominant of the soft precipitates on the COF behavior; (c-) as a consequence of the reduced strain energy and tangential load, the local COF decreased when the abrasive scratches the hard precipitates; (d-) regarding the depth of penetration and removed volume, the numerical results are in accordance with the experimental results; (e-) there is not a remarkable micro-mechanism transition using the approach of the dimensional wear coefficient as a function of normal load, which indicates that several abrasive micro-mechanisms can occur in a single scratching; however, a predominance of a certain micro-mechanism can be observed; (f-) hard precipitates often decreases the local depth of penetration and, as a consequence, they cause the reduced of removed volume and increased the local specific energy; (g-) considering the studied range of the normal load, soft precipitates follow the matrix mass removal behavior, but these particles can show fluctuations of the local specific energy in the less severe abrasion; and, finally, (h) the map of the abrasive resistance x deformed hardness/attack angle is an important tool to point out the dominant ductile or brittle effect on the microstructure (mechanical properties); and it delineates frontiers for the abrasive micromechanisms.